Changes in the fatty acid profile in erythrocytes in high-level endurance runners during a sports season - Vas, F. J. A.; Pérez, J. G.; Toro-Román, V.; Sánchez, I. B.; Mariño, M. M.; Vicho, B. G. (Nutrients, 2024)
Fatty acids (FAs) are an essential component of the erythrocyte membrane, and nutrition and physical exercise are two variables that affect their structure and function. The aim of this study was to evaluate the erythrocyte profile in a group of high-level endurance runners, as well as the changes in different FAs, throughout a sports season in relation to the training performed. A total of 21 high-level male endurance runners (23 ± 4 years; height: 1.76 ± 0.05) were evaluated at four different times throughout a sports season. The athletes had at least 5 years of previous experience and participated in national and international competitions. The determination of the different FAs was carried out by gas chromatography. The runners exhibited low concentrations of docosahexaenoic acid (DHA) and omega-3 index (IND w-3), as well as high values of stearic acid (SA), palmitic acid (PA), and arachidonic acid (AA), compared to the values of reference throughout the study. In conclusion, training modifies the erythrocyte FA profile in high-level endurance runners, reducing the concentrations of polyunsaturated fatty acids (PUFAs) such as DHA and AA and increasing the concentrations of saturated fatty acids (SFAs) such as SA and the PA. High-level endurance runners should pay special attention to the intake of PUFAs w-3 in their diet or consider supplementation during training periods to avoid deficiency.